2017
DOI: 10.1080/02670836.2016.1230168
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the small punch tensile behaviour of an aerospace alloy

Abstract: The small punch (SP) test is a widely accepted methodology for obtaining mechanical property information from limited material quantities. Much research has presented the creep, tensile and fracture responses of numerous materials gathered from small-scale testing approaches. This is of particular interest for alloy down selection of next-generation materials and in situ mechanical assessments. However, to truly understand the evolution of deformation of the miniature disc specimen, an accurate and detailed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The SP curves obtained in this study are qualitatively similar to those reported in the literature for other investigations on EBM AM Ti64 [17][18][19][20], and differ significantly from conventional SP test records for steel specimens, as in the example illustrated in Fig. 2.…”
Section: General Remarkssupporting
confidence: 88%
See 1 more Smart Citation
“…The SP curves obtained in this study are qualitatively similar to those reported in the literature for other investigations on EBM AM Ti64 [17][18][19][20], and differ significantly from conventional SP test records for steel specimens, as in the example illustrated in Fig. 2.…”
Section: General Remarkssupporting
confidence: 88%
“…The available literature on the application of various SP testing techniques, including fatigue and creep, to various types of Ti64 (forged, cast, and EBM) [17][18][19][20]41] demonstrates a significant level of interest in the material testing community. Published force-displacement curves of AM specimens [17][18][19][20] are similar to those we obtained in this study. Several references also show significantly lower tensile properties for AM Ti64 with respect to forged and cast material, as inferred from SP tests performed both at ambient and elevated temperatures [17,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…SP test is possible to apply to evaluation of strength in any aging time and predict the residual life. However, the load in the SP test sample is complex and scattered [6], so that detailed study on SP are required not only in stress distribution but also chemical reaction mechanism furthermore.…”
Section: Resultsmentioning
confidence: 99%
“…Small punch tensile testing induces a complex biaxial stress state in test specimens [21,[30][31][32]. The load-displacement curves obtained from SPT tests typically exhibit up to four distinct bending regions [33], as shown in Figure 2, and there is currently no analytical solution available that allows strain to be calculated from all four bending regions without finite element analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%